2020
DOI: 10.21203/rs.3.rs-34165/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prognostic role of pre-sarcopenia and body composition with long-term outcomes in obstructive colorectal cancer: a retrospective cohort study

Abstract: Background: The clinical significance of pre-sarcopenia in colorectal cancer obstruction has not yet been described. The present study aimed to determine the short and long-term oncologic impacts of pre-sarcopenia in obstructive colorectal cancer.Methods: We retrospectively analyzed 214 patients with obstructive colon cancer between January 2004 and December 2013. Initial staging computed tomography (CT) scans identified pre-sarcopenia and visceral obesity by measuring the muscle and visceral fat areas at the … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…In this cohort study, regarding patients who underwent upfront rectal cancer surgery without NACR, the presence of preoperative sarcopenia assessed at CT scan was an independent prognostic factor for dismal longterm OS and TSS, along with other acknowledged variables such as the tumor stage. Several other studies have reported an association between preoperative skeletal muscle wasting and poor long-term survival in different oncological diseases [5][6][7][8]33] and more specifically in colorectal cancer patients [15,[34][35][36][37][38]. However, all those trials used a combined analysis of colon and rectal cancer patients and this may have generated an ambiguous interpretation regarding the oncologic prognosis since colonic tumors have a better survival than rectal cancers [21][22][23]39].…”
Section: Discussionmentioning
confidence: 99%
“…In this cohort study, regarding patients who underwent upfront rectal cancer surgery without NACR, the presence of preoperative sarcopenia assessed at CT scan was an independent prognostic factor for dismal longterm OS and TSS, along with other acknowledged variables such as the tumor stage. Several other studies have reported an association between preoperative skeletal muscle wasting and poor long-term survival in different oncological diseases [5][6][7][8]33] and more specifically in colorectal cancer patients [15,[34][35][36][37][38]. However, all those trials used a combined analysis of colon and rectal cancer patients and this may have generated an ambiguous interpretation regarding the oncologic prognosis since colonic tumors have a better survival than rectal cancers [21][22][23]39].…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the OCRC, CT-based myopenia was significantly associated with obstruction [16]. Lee et al showed that SMI-low status was significantly associated with poor OS and RFS, whereas the status was not associated with postoperative complications in 214 OCRC patients [44]. In their study, SEMS were inserted in 117 (54.7%), stoma was created in 41 (19.2%), transfusion was administered to 107 (50.0%), and emergency surgery was performed in 15 cases (7.0%).…”
Section: Discussionmentioning
confidence: 99%
“…Tumor biomarkers have been widely used in the diagnosis and post-treatment follow-up of patients with CRC [15]. The latest research shows that Pre-sarcopenia is a clinical factor significantly associated with OS and DFS in obstructive colorectal cancer [16]. Traditionally, CEA is one of the tumor biomarkers used to predict recurrence, prognosis, and treatment effect in these patients [17,18].…”
Section: Discussionmentioning
confidence: 99%